Super-micro-bland particle embolization combined with RF-ablation: angiographic, macroscopic and microscopic features in porcine kidneys - Sommer, Christof-Matthias; Kortes, Nikolas; Mogler, Carolin; Bellemann, Nadine; Holzschuh, Maria; Arnegger, Florian; Nickel, Felix; Gehrig, Tobias; Zelzer, Sascha; Meinzer, Hans-Peter; Longerich, Thomas; Stampfl, Ulrike; et al. (European journal of radiology, 2012)
Purpose: To describe angiographic, macroscopic and microscopic features of super-micro-bland particle embolization in combination with RF-ablation in kidneys. Thereby, a special focus was given on the impact of the sequence of the different procedural steps. Materials and methods: In ten pigs, super-micro-bland particle embolization combined with RF-ablation was carried out. Super-micro-bland embolization was performed with spherical particles of very small size and tight calibration (40±10μm). In the left kidneys, RF-ablations were performed before embolization (I). In the right kidneys, RF-ablations were performed after embolization (II). The animals were killed three hours after the procedures. Angiographic (e.g. vessel architecture), macroscopic (e.g. long and short axes of the RF-ablations) and microscopic (e.g. particle distribution) study goals were defined. Results: Angiography detected almost no vessels in the center of the RF-ablations in I. In II, angiography could not define the RF-ablations. Macroscopy detected significantly larger long and short axes of the RF-ablations in II compared to I (52.2±3.2mm vs. 45.3±6.9mm [P<0.05] and 25.1±3.5mm vs. 20.0±1.9mm [P<0.01], respectively). Microscopy detected irregular particle distribution at the rim of the RF-ablations in I. In II, microscopy detected homogeneous particle distribution at the rim of the RF-ablations. Microscopy detected no particles in the center of the RF-ablations in I and II. Conclusion: The sequence of the different procedural steps of super-micro-bland particle embolization combined with RF-ablation impacts angiographic, macroscopic and microscopic features in kidneys in the acute setting.